(untitled) (Fiep Bulletin - online, 2020)
The constant search for evaluation processes that will be as reliable as those already used, has been widely discussed today. This study aims to trace the possible correlation between the BIO method and Faulkner’s formula, making a comparison with studies already developed on the subject. Relating the data found in the current study, which analyzed 20 students practicing bodybuilding and the works cited below. Significant results were found showing a close relationship between studies, showing correlation (r = 0.97), so studies of this kind deserve a level of deepening by the scientific community. The data obtained through the correlation (r) between the methods, present us strong correlation between them, however, it is wrong and wrong to affirm that these methods are reliable for the evaluation of athletes with high trainability index, without any previous scientific evaluations. . Thus, the use of the current methods becomes effective and relevant for the analyzed public, considering that they are regular students of bodybuilding, which mostly seek greater concepts and in-depth knowledge about body practices and their evaluations.